UPAYA PENANGANAN DAN PENCEGAHAN PEMERINTAH INDONESIA TERHADAP KASUS PENYANDERAAN WARGA NEGARA INDONESIA OLEH KELOMPOK ABU SAYYAF - Meilinda Triana Pangaribuan; Ali Abdullah Wibisono; Benny Josua Mamoto (Jurnal Pemerintahan dan Politik, 2022)
This study goals to explain for the crimes that happen inside the Sulu Sea including kidnapping Indonesian citizens including the hostage of Indonesian citizens who led to the demand for ransom. This study uses qualitative research methods and the data sources are from studies of journals or reports from institutes or scientific writing. The reason of this study is to provide an explanation for how the Indonesian Government manages the kidnapping and Indonesia Goverment has the obligation to maintain the safety and security of its citizens, including the hostage incident by the Abu Sayyaf group and to provide an overview of the prevention efforts carried out. To analyze in this study, the author uses the concepts and theories are maritime piracy, maritime security, and international cooperation. The outcomes of this study, the handling of hostage-taking Indonesian citizens (WNI) by the Abu Sayyaf changed into carried out by the Government of Indonesia by conducting negotiations, both closed and open negotiations. Prevention efforts executed by the Government of Indonesia are by establishing cooperation Indomalphi with Malaysia and the Philippines. After the Indomalphi cooperation, there is no data showing the recurrence of Indonesian citizens being held hostage by the Abu Sayyaf group. The recommendation of advice in this paper is as a long-term prevention effort is the establishment of regional development cooperation and economic development between Indonesia and the southern Philippines. Cooperation in the field of culture, education, and in the social field. So that the cooperation is expected to build a close relationship between the two countries (sister city) can prevent the Abu Sayyaf group from kidnapping and hostage to Indonesian citizens.